THE USAGE OF COMPUTER-AIDED ENGINEERING SYSTEM “SOLIDWORKS MOTION” TO SOLVE THE PROBLEMS OF KINEMATICS AND DYNAMICS OF TECHNICAL SYSTEMS - MARCHENKO, MAKSYM; KHARZHEVSKYI, VIACHESLAV; TKACHUK, VITALII; HORIASHCHENKO, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper is dedicated to the problems of engineering analysis of technical systems by means of computer modeling, in particular the calculation of kinematic and dynamic characteristics of mechanisms and machines using the Computer-Aided Engineering system – SOLIDWORKS Motion, that allows to conduct numerical experiments to check the working capacity of mechanisms and machines, determine their main kinematical and dynamical characteristics, including for the purpose of further optimization according to various criteria. The paper shows results of the performed calculations of various types of mechanisms using examples used in the academic process within the course "Theory of Mechanisms and Machines", which can be also successfully used within the design process, and includes examples of kinematic and dynamic analysis of linkage mechanisms, cam mechanisms, gear trains. In particular, the paper includes the simulation of the work process of the robot-manipulator using SOLIDWORKS Motion. It is shown that the usage of modern Computer-Aided Engineering systems (like SOLIDWORKS Motion or similar) enables to simplify the design process, shorten the design time and give an ability to carry out multi-parametric optimization procedures using different criteria, such as displacement values, velocities, accelerations, the values of reaction forces, overall dimensions etc. Besides, the usage of CAE-technologies enables to transform the academic process and makes it much more interesting or the students, who can use such technologies in their professional work in the future and become more competitive in the job market.